THE INLUENCE OF SOCIAL MEDIA MARKETING AND BRAND IMAGE ON CONSUMER PURCHASING DECISIONS AT TYPICAL BAKMIE KHAS JAKSEL MAYESTIK - Renaldi Syahputra (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This study aims to analyze the influence of social media marketing and brand image on consumer purchase decisions in Bakmie Khas Jakarta, Mayestik. The main problem identified in this study is the decline in sales due to less than optimal digital marketing strategies and brand images that have not been firmly formed in the minds of consumers. This study uses a quantitative method, with a purposive sampling technique to collect data from respondents who are consumers of Bakmie Khas Jakarta Mayestik. The main instrument in this study is a questionnaire distributed to the respondents, then analyzed using multiple linear regression analysis to test the relationship between variables. The results of the study show that social media marketing has a positive and significant effect on purchasing decisions, which means that a more effective digital marketing strategy can increase consumer buying interest. In addition, brand image also has a significant influence on purchasing decisions, showing that a strong brand image can increase customer loyalty. Simultaneously, social media marketing and brand image have a significant influence on consumer purchasing decisions, which emphasizes the importance of digital marketing strategies and brand management in improving the competitiveness of culinary businesses.